E-Commerce Risk of Food Product to Consumer Purchase Decisions in Kalimantan Barat - Zulfikri; Dolorosa, Eva; Kurniati, Dewi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
The increase in internet users and the trend of online food shopping have created risks that affect consumer purchase decisions when buying food products online. This research aims to examine how risk perception influences the purchasing decisions of online food products. This study was conducted in Pontianak, Kalimantan Barat. The region's expanding digital infrastructure offers significant e-commerce growth opportunities in the food sector. However, uncertainties and perceived risks may pose challenges for both consumers and the local industry. The sample was determined using convenience sampling. The data collected was primary data obtained from a questionnaire completed by 150 consumers of online food products. The variables involved in this research were financial risk, product risk, time risk, delivery risk, and consumer purchase decisions. The data analysis utilized Structural Equation Modelling (SEM) within a quantitative framework to explore and validate relationships between key variables. This included descriptive analysis to summarize data characteristics and Partial Least Squares (PLS) testing with SmartPLS 4 software. This approach will offer a thorough overview of the data and a detailed analysis of structural relationships. The research shows that delivery risk, financial risk, and product risk significantly affect consumer purchasing decisions, with delivery risk being the most influential. Changes in delivery risk will notably impact buying behaviour. In contrast, time risk does not significantly impact purchasing decisions, as evidenced by a path coefficient (0.069), t-value (1.007<t-table 1.96), and p-value (0.314>0.05).